2020
DOI: 10.1186/s12909-020-02239-6
|View full text |Cite
|
Sign up to set email alerts
|

How to assess? Perceptions and preferences of undergraduate medical students concerning traditional assessment methods

Abstract: Background Medical students’ perception of traditional assessments have an important impact on their approaches to learning. Even though these assessment formats such as Multiple-Choice Question (MCQ), Short Answer Question (SAQ) or oral examinations, are frequently used in medical curricula, only little is known about student’s perceptions of these assessments. The objective of this study was to assess perceptions and preferences of undergraduate medical students concerning traditional assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
1
20
1
Order By: Relevance
“…Particularly, study courses with extensive practical and interactive components such as medical education faced major challenges to protect students, faculty and patients, and flatten the curve by social distancing while ensuring the educational mission at the same time. Undergraduate medical education usually applies many different formats in teaching (i.a., bedside-teaching, laboratory courses, practical training) and in assessment (i.a., Multiple-Choice-Questions, Objective Structured Clinical Examinations, mini-clinical evaluation exercise) (Holzinger et al, 2020;Vanderbilt et al, 2013). In response to COVID-19, many medical schools worldwide shut down undergraduate medical education and converted most of their teaching to digital formats (Rose, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, study courses with extensive practical and interactive components such as medical education faced major challenges to protect students, faculty and patients, and flatten the curve by social distancing while ensuring the educational mission at the same time. Undergraduate medical education usually applies many different formats in teaching (i.a., bedside-teaching, laboratory courses, practical training) and in assessment (i.a., Multiple-Choice-Questions, Objective Structured Clinical Examinations, mini-clinical evaluation exercise) (Holzinger et al, 2020;Vanderbilt et al, 2013). In response to COVID-19, many medical schools worldwide shut down undergraduate medical education and converted most of their teaching to digital formats (Rose, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This student's mix assessment format preference was also shown in the previous study. [15] The corona virus pandemic has introduced novel methods of delivering education to medical students. Lectures have rapidly been developed to be delivered online as webinars using various platforms such as Zoom, with such technologically enhanced approaches already being proven to have high levels of engagement with medical students.…”
Section: Graph 1 Student's Gender and Their Locationmentioning
confidence: 99%
“…Moving forward, we should be well prepared and include oral examination in a schedule. Since previous research findings showed that the assessment format will have a considerable influence on student's approaches to learning [15], we will consider announcing the schedule earlier at the beginning of the block. b) Difference perception in lecturer's scoring and Fraud Risk due to Items Leakage Cees van der Vleuten [18] stated that the utility of an assessment method depends on its reliability, validity, costs, educational impact, and its acceptability.…”
Section: Online Oral Examination Challenges and Future Work A) Scheduled Oral Examinationmentioning
confidence: 99%
See 2 more Smart Citations